RCA-PCR: A ROBUST TECHNIQUE FOR THE DETECTION OF TOMATO LEAF CURL NEW DELHI VIRUS-POTATO AT ULTRA LOW VIRUS TITRE - Jeevalatha, A; Singh, BP; Kaundal, Priyanka; Kumar, Ravinder; Raigond, Baswaraj (Potato Journal, 2014)
Â Â